SAVING THE FOOD CROPS OUR GRANDPARENTS GREW - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Members of traditional communities in all ACP countries have a unique understanding and interpretation of their surroundings. This includes an understanding of the crops and weeds that are used for food and medicine and their relationship to the...